Cytomegalovirus shedding from breastmilk and mucosal sites in healthy postpartum women: A pilot study. Issue 5 (3rd January 2019) - Azenkot, Tali; Zaniello, Benjamin; Green, Margaret L.; Selke, Stacy; Huang, Meei‐li; Magaret, Amalia; Wald, Anna; Johnston, Christine
Abstract : Mother‐to‐child cytomegalovirus (CMV) breastmilk transmission can occur in the postnatal period. In a pilot study, we measured daily CMV detection by polymerase chain reaction in breastmilk, vaginal, and saliva samples from nine healthy CMV‐seropositive postpartum women for 28 days. CMV was found in seven of nine women and 171 of 253 breastmilk samples (67.6%). In four women, all breastmilk samples were positive. CMV was less frequently detected in the vagina (39 of 258, 15.1%) and saliva (53 of 258, 20.5%). Daily breastmilk, oral, and genital collection is feasible and demonstrates high variability between women. Further study of the dynamics of CMV in distinct anatomic compartments is warranted. Highlights: 1. Daily sampling of breastmilk and mucosal samples in healthy, postpartum women is feasible. 2. CMV is detected consistently in breastmilk in some women, but shedding patterns are highly variable between women. 3. Oral and vaginal CMV shedding occur less frequently than breastmilk CMV shedding, suggesting anatomic compartmentalization of viral replication.